Being Stuck in America: Challenges to Liquid Modernity - Šesnić, Jelena (2011)
Based on a reading of recent US American fiction, it is argued that new realist tendencies have been launched as a reaction to the New Gilded Age and to the exigencies of, what Zygmunt Bauman terms, liquid modernity. Further, reconsideration of some terms such as the body, labour, the new poor is offered in the framework of the latest phase of global modernity.
Projekt MZOS
ENG